2015
DOI: 10.11114/jets.v3i2.666
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Teacher Effectiveness through Hierarchical Linear Models: Exploring Predictors of Student Achievement and Truancy

Abstract: This study explored significant predictors of student's Grade Point Average (GPA) and truancy (days absent), and also determined teacher effectiveness based on proportion of variance explained at teacher level model. We employed a two-level hierarchical linear model (HLM) with student and teacher data at level-1 and level-2 models, respectively. Using the data from one of the largest urban school districts in the United States, the analysis identified several significant intervening and demographic predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In fact, estimates of teacher effects on student achievement vary widely depending on the nature of the study and what is measured (see Stronge, , for a review). Recently, Subedi et al (), using hierarchical linear modeling, reported the percentages of variance explained at the teacher level on student outcomes ranged from 12.4% (GPA, d = 0.35) to 15% (days absent, d = 0.39). In comparison, however, with student (∼50%) and environmental (e.g., home/SES factors = up to 10%) variables, teacher impact on actual student achievement is relatively small (Stronge, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, estimates of teacher effects on student achievement vary widely depending on the nature of the study and what is measured (see Stronge, , for a review). Recently, Subedi et al (), using hierarchical linear modeling, reported the percentages of variance explained at the teacher level on student outcomes ranged from 12.4% (GPA, d = 0.35) to 15% (days absent, d = 0.39). In comparison, however, with student (∼50%) and environmental (e.g., home/SES factors = up to 10%) variables, teacher impact on actual student achievement is relatively small (Stronge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Bronfenbrenner's bioecological systems theory (Bronfenbrenner & Morris, ), Lerner's relational developmental systems model (Lerner et al, ), and associated studies indicated that learning was affected by numerous intersecting within‐student and outside‐the‐student systems and factors, such as quality of schooling, sociofamilial relationships and support for learning, and socioeconomic status (SES). In other words, an ecological perspective posits that individual student outcomes are influenced by a variety of complex factors operating across systems (e.g., Eccles & Roeser, ; Konstantopoulos, ; Stronge, ; Subedi, Reese, & Powell, ), suggesting student outcomes be viewed in light of an ecological or systems perspective.…”
Section: School Counseling Role and Challengesmentioning
confidence: 99%
“…In a review of five studies on teacher effectiveness, Rice (2003) found that teachers who have earned advanced degrees have a positive impact on high school mathematics and science achievement when the degrees earned were in these subjects. In past, Subedi, Reese, and Powell (2015) found a significant positive effect of teacher's degree (education) level on student's high school GPA. The simple truth is that the public education cannot fulfill its mission if students growing up in poverty, students of color and low-performing students continue to be disproportionately taught by inexperienced, under-qualified teachers (Peske & Haycock, 2006).…”
Section: Review On Predictors Of Highly Effective Teachers Searching mentioning
confidence: 96%
“…Ehrenberg ve Brewer (1994) ise öğretmen niteliklerinin öğrencilerin test puanlarını etkileyebildiğini ve bu nedenle öğretmen niteliklerinin öğrencilerin test puanlarına olan etkisinin analiz edilmesi gerektiğini vurgulamaktadır. Bu konuda yapılan çalışmalarda öğretmenlerin deneyimleri, eğitim düzeyleri, mesleğe karşı tutumları, mesleki sertifikalara sahip olmaları gibi değişkenlerin öğrenci başarısına etki eden öğretmen niteliklerinden olduğu belirtilmektedir (Dodeen ve diğerleri, 2012;Maphoso ve Mahlo, 2015;Musau ve Abere, 2015;Ojera, 2016;Subedi, Reese ve Powell, 2015).…”
Section: Introductionunclassified